Degree Of Security And Safety Factors Availability In Teaching Throwing And Jumping Activities For Students Studying Athletics Curricula In Faculty Of Physical Education At Yarmouk University From Their Viewpoint (Journal of Namibian Studies : History Politics Culture, 2023)
The study aimed to identify the degree of security and safety factors available in teaching throwing and jumping activities for students studying athletics curricula at the Faculty of Physical Education at Yarmouk University from their viewpoint. The researchers used the descriptive approach to suit the nature and objectives of the study. After reviewing the theoretical literature and previous studies, the researchers built the study tool (questionnaire) in accordance with the nature and objectives of this study. The study tool consisted of• axes and (20) paragraphs that were answered through the five-point Likert scale. The community study consists of the students of the Faculty of Physical Education registered in the throwing and jumping activities, numbering (442) male and female students, while the study sample was (126) male and female students. For the statistical process of the data, the researchers used the statistical processing program (SPSS) through the use of several mathematical operations (arithmetic average, standard deviation, t-test, and one-way analysis of variance). Results showed that the degree of availability of security and safety factors in the courses of throwing and jumping activities at the Faculty of Physical Education at Yarmouk University came with an average degree, and it also showed that there were statistically significant differences depending on the gender variable in the axis of handling tools and sports devices safely and were in favor of males. The results also showed that there were no statistically significant differences depending on the academic year variable. The researchers recommend working to raise students' awareness of the safety and security factors that should be applied during the teaching of throwing activities so that they become a behavior that students get used to.